The Development and User Acceptance Survey of Astaxanthin Infused Topical Moisturizer - Rahim, Nur Izzati; Rusmidi, Muhamad Helmi Husaini; Radzun, Khairul Adzfa (Journal of Asian Scientific Research, 2022)
Astaxanthin was a beneficial carotenoid in the nutraceutical, food, cosmetics, and feed industries. The new astaxanthin infused topical moisturizer was developed using astaxanthin, Manuka honey, and Neutrogena Hydro Boost gel moisturizer. The astaxanthin was extracted from Haematococcus pluvialis subjected to the in-house astaxanthin extraction procedure developed by the Microalgae Research Laboratory, UiTM Puncak Alam, Selangor. Fifteen topical moisturizer samples were developed via Box-Behnken Design. The moisturizer properties were significantly influenced by astaxanthin, Neutrogena Hydro Boost gel moisturizer, and Manuka honey content based on the User Acceptance Survey done on 250 respondents. This study observed response surface regression, analysis of variance, and response optimization for appearance, aroma/smell, and texture. The optimum levels of the three factors were astaxanthin is at 1 ml, Neutrogena Hydro Boost gel moisturizer is at 20 ml, and Manuka honey must be less than 10 g which is at 0.9192g, as 69% of respondents like the composition.